Analysis of the Virtual Experiment of the Roller in Dredger Grab Machine - Xu Cijun (Jixie chuandong)
The driving roller in dredger grab machine has the characteristic of limited installation space and complicated load condition,is an effective supporting connector which ensures the machine works safely.According to the virtual prototype of dredger built on simplified model of mooring system,the virtual experiment model of driving roller is constructed between pedestals and workbench of grab machine.And according to the restriction of adding contact of the forces applied on the roller during the motion process of the grab machine,the statics analysis and dynamics analysis are carried out based on ADAMS software.The force curve of driving roller is fitted into subsection function and the finite element model is constructed in ANSYS,so that the stress distribution and the displacement deformation can be analyzed in time domain.The analysis results show that virtual experiment of driving roller in dredger grab machine effectively finds out the failure condition of roller during the working process of grab machine,and a reliable simulation model to its structure optimization as well as mechanical structure analysis on the offshore work platform is provided.